Anticonvulsant Potential of Certain New (2E)-2-[1-Aryl-3-(1H-imidazol-1-yl)propylidene]-N-(aryl/H)hydrazinecarboxamides - Mohamed I. Attia; Mohamed N. Aboul-Enein; Aida A. El-Azzouny; Yousreya A. Maklad; Hazem A. Ghabbour (The Scientific World Journal)
Anticonvulsant potential and neurotoxicity of certain new imidazole-containing arylsemicarbazones 6a–p are reported. The test compounds 6a–p exhibited anticonvulsant activity mainly in the scPTZ screen. Compound 6p emerged as the most active surrogate displaying 100% protection at a dose level of 636 μmol/kg in the scPTZ screen without any neurotoxicity. The assigned (E)-configuration of the title compounds 6a–p was confirmed via single crystal X-ray structure of compound 6g.